Thick translations and thick contextualisation in two english versions of laozi by Lin Yutang and ames and hall - Huang, Weixing (2020)
Laozi is recognized as a fundamental and the earliest scripture of Daoism philosophy. It has profound philosophical thoughts and was written in a pithy style. There is a distinct cultural difference between China and the English speaking countries and a distinct linguistic difference between the Chinese and English languages. These factors present a formidable challenge to translators and make comprehending Laozi’s thoughts a difficult task. It is essential to present the cultural, social, and historical contexts of Laozi for a better and deeper understanding of its translations. Thick translation, which aims to produce thick contextualized texts, is crucial to comprehending Laozi translations. Although researchers have studied Laozi translations extensively, many overlooked the importance of context. This study presents a comparison of two English versions of Laozi from the perspective of thick translation theory in an attempt to reveal how thick translations contribute to achieving thick contextualization. One version was translated by Nobel Prize Nominee in Literature Lin Yutang and the other version was translated by famous philosophers Roger T. Ames and David L. Hall. Lin translated Laozi from his native language to a foreign language while Ames and Hall translated Laozi from a foreign language to their native language. This comparison identifies similarities and differences of three types of thick translations, namely, textclose, text-remote, and text-self. This study investigates all thick translations appearing in the two selected versions and illustrates their characteristics with typical examples of each type of thick translation.